2015
DOI: 10.1038/ajg.2015.52
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease in Immigrants to Canada And Their Children: A Population-Based Cohort Study

Abstract: Younger age at arrival to Canada increased the risk of IBD in immigrants. Canadian-born children of immigrants from some regions assumed the high Canadian incidence of IBD, indicating that the underlying risk is activated with earlier life exposure to the Canadian environment in certain groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
143
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(157 citation statements)
references
References 21 publications
10
143
1
3
Order By: Relevance
“…Mortality remains increased in both the short and longer term for these patients, a point again confirmed in the current study. A recent meta-analysis by Chen et al 6 also suggests CDI is a risk factor for colectomy in IBD patients, supporting the conclusions of this current study and patients should be counselled accordingly. Antibiotic therapy remains the standard of treatment as in non-IBD-infected individuals, 7 although there is an increasing body of work in recent years to suggest faecal microbiota may have an important role to play, 8 although further studies are needed.…”
Section: Linked Contentsupporting
confidence: 72%
See 1 more Smart Citation
“…Mortality remains increased in both the short and longer term for these patients, a point again confirmed in the current study. A recent meta-analysis by Chen et al 6 also suggests CDI is a risk factor for colectomy in IBD patients, supporting the conclusions of this current study and patients should be counselled accordingly. Antibiotic therapy remains the standard of treatment as in non-IBD-infected individuals, 7 although there is an increasing body of work in recent years to suggest faecal microbiota may have an important role to play, 8 although further studies are needed.…”
Section: Linked Contentsupporting
confidence: 72%
“…4 The Stan- The findings of this study add to the growing body of evidence supporting the complex role of environmental factors in modulating IBD risk. The Swedish population-based study by Li et al 5 and the Canadian population-based study by Benchimol et al 6 suggested that low-risk migrants over subsequent generations adopt the risk of the country to which they migrated. Consistent with the findings of the present study, our group also demonstrated an increased risk of IBD in migrants from a high incidence region, UK, to Canterbury, New Zealand where IBD incidence had previously been low.…”
mentioning
confidence: 99%
“…However, the same group found that although the incidence of CD had increased over time in both Europeans and South Asians, the incidence was significantly lower in South Asians as compared to Europeans [31] . In another migrant study, Benchimol et al [32] compared the incidence of IBD among immigrants and non-immigrants of Ontario, Canada, and found that the incidence of IBD among the immigrants was significantly lower that of the resident population (7.3/100,000 vs. 23.9/100,000). However, the incidence of IBD among the children of these immigrants was significantly higher than that of their parents and approached that of non-immigrants ( Fig.…”
Section: Migrant Epidemiologymentioning
confidence: 99%
“…Nevertheless, it will be keen at creeping among those who, deliberately or forcefully, have left home behind, to face an abrupt encounter with a different (westernized) pattern of life. Such a scenario has recently been described (33) for thousands of North Africans or South American people, who moved to Canada. Following them up for a relatively short time, the investigators found that, by the second generation (at the latest), the risk of these immigrants to develop IBD matched the figures of the native Canadians.…”
Section: Diffusion Of Inflammatory Bowel Disease Among Immigrantsmentioning
confidence: 99%